Pesticide Contamination in Indian Agricultural and Residential Areas: A Comparative Assessment of Health Risks and Environmental Impacts - Riya Raj C.A.; Nandini Katare; Don Caeiro; Mayank David Raiborde (Indian Journal of Forensic Medicine and Pathology, 2026)
The extensive use of pesticides in India, particularly in agriculturally intensive regions, has raised significant concerns regarding environmental contamination and associated human health risks. This review synthesizes recent evidence on pesticide residue occurrence in water, milk, vegetables, and soil, with special emphasis on high-risk agricultural districts of Chhattisgarh and comparable regions. Data were compiled from government databases, peer-reviewed literature, and empirical field-based analytical studies employing standardized protocols (APHA, AOAC) and advanced instrumental techniques such as GC–MS, GC–MS/MS, HPLC-PDA, AAS, ICP–MS, and HPTLC. Findings indicate widespread detection of organophosphates, organochlorines, and pyrethroids—including carbaryl, chlorpyrifos, malathion, diazinon, deltamethrin, quinalphos, and 4,4′- DDT—in environmental and food matrices. Several studies reported exceedance of acceptable daily intake (ADI) and acute reference dose (ARfD) values, particularly among children, highlighting elevated vulnerability. Health risk assessments utilizing Hazard Quotient (HQ), Hazard Index (HI), Target Hazard Quotient (THQ), and Lifetime Cancer Risk (LCR) models revealed potential noncarcinogenic and carcinogenic risks in areas proximal to pesticide application sites.These compounds exert toxicity primarily through mechanisms such as acetylcholinesterase inhibition, endocrine disruption, oxidative stress induction, and bioaccumulation, contributing to both acute and chronic health effects. Spatial analyses further demonstrated contamination hotspots near agricultural spraying zones, while seasonal variation influenced physicochemical water quality and pollutant persistence. Despite regulatory efforts, critical research gaps remain, including limited longitudinal monitoring, inadequate evaluation of cumulative and mixture toxicity, insufficient exploration of non-agricultural contamination sources, and weak implementation strategies for sustainable alternatives.The review underscores the urgent need for integrated surveillance systems, farmer education on safe pesticide handling, improved regulatory enforcement, and adoption of sustainable pest management strategies. Strengthening evidence-based policymaking is essential to safeguard environmental integrity, public health, and long-term agricultural sustainability.